2015
DOI: 10.1007/s12185-015-1801-5
|View full text |Cite|
|
Sign up to set email alerts
|

Infusion of donor lymphocytes expressing the herpes simplex virus thymidine kinase suicide gene for recurrent hematologic malignancies after allogeneic hematopoietic stem cell transplantation

Abstract: The infusion of donor lymphocytes expressing the herpes simplex virus thymidine kinase suicide gene (TK-cells) is a promising strategy for the treatment of hematologic malignancies relapsing after allogeneic hematopoietic stem cell transplantation. Here we report the results of a phase I clinical trial designed to examine the feasibility, safety, and efficacy of donor lymphocyte infusion (DLI) of TK-cells. Three patients (two with malignant lymphomas, one with acute myeloid leukemia) were enrolled in the trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…There was no local or systemic toxicity related to infusion, and no severe GVHD requiring systemic steroid and/or ganciclovir administration. 95 These results suggest that infusion of TK cells might be beneficial to facilitate immune reconstitution, augmenting GVL effect, with GVHD and its associated mortality being controllable.…”
Section: Gvhd and Gvl After DLImentioning
confidence: 92%
See 1 more Smart Citation
“…There was no local or systemic toxicity related to infusion, and no severe GVHD requiring systemic steroid and/or ganciclovir administration. 95 These results suggest that infusion of TK cells might be beneficial to facilitate immune reconstitution, augmenting GVL effect, with GVHD and its associated mortality being controllable.…”
Section: Gvhd and Gvl After DLImentioning
confidence: 92%
“…19 The expression of herpes simplex thymidine kinase suicide gene was confirmed to promote immune reconstitution and GVT effect, and reduce risk of GVHD in DLI. 95 Moreover, ganciclovir can be given to abort GVHD when necessary. Ciceri et al 96 performed a multicenter non-randomized phase I-II study that 28 patients undergoing haploidentical SCTs received donor lymphocytes expressing herpes simplex thymidine kinase suicide gene (TK cells) starting 28 days after transplantation.…”
Section: Gvhd and Gvl After DLImentioning
confidence: 99%
“…DLI of TK cells was safely performed in a total of eight patients. However, these TK cells disappeared rapidly, probably due to their insufficient in vivo expansion in these patients [77,78]. A comparison of onset with remission of acute GVHD confirmed that TK cells were predominantly eliminated and that proliferative CD8(+) non-TK cells were also depleted in response to ganciclovir administration.…”
Section: Suicide Gene Therapymentioning
confidence: 88%
“…With the long-term prophylactic administration of acyclovir, TK cells expanded oligoclonally, and the frequency of splice variants of TK cells increased. Known cancer-associated genes were not evident near the oligoclonally expanded HSV-TK insertion sites [78,79].…”
Section: Suicide Gene Therapymentioning
confidence: 95%
“…Each TCR Vb segment was amplified with one of the 24 Vb subfamilyespecific primers and a Cb primer. The sequences of primers Cb and Vb1 to 24 and spectratyping analysis was performed as reported previously [19]. The amplified PCR products were size-fractionated by capillary gel electrophoresis with the use of an ABI model 3130 Genetic Analyzer, and data were analyzed with the use of GeneMapper software v4.0 (Applied Biosystems).…”
Section: Tcr Vb Analysis By Means Of Spectratypingmentioning
confidence: 99%